PILLAR INDEX AND REGIONAL DEVELOPMENT: AN INTEGRATED APPROACH TO ECONOMIC AND SOCIAL PROGRESS : ISBN 978-630-95064-7-4 - Bagijo, Himawan Estu (Technium Books, 2025)
The book: PILLAR INDEX AND REGIONAL DEVELOPMENT: AN INTEGRATED APPROACH TO ECONOMIC AND SOCIAL PROGRESS is published in Technium. Editors: Amodu, Salisu Ameh, PhD Prof. Dr. Bohari Mohd Yamin